2019
DOI: 10.1016/j.athoracsur.2018.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Expert Consensus Document on Pulmonary Metastasectomy

Abstract: When managing nonseminomatous germ cell tumors, contralateral lung abnormalities ≤ 10 mm can be observed if histology of unilateral PM demonstrates complete tumor necrosis. 17. When managing nonseminomatous germ cell tumors, PM is indicated for select patients with limited number of lung abnormalities after first or second-line platin-based chemotherapy suspected of containing viable nonseminomatous cancer and/or malignant transformation of teratoma into non-germ cell cancer. 18. In breast cancer patients, PM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
178
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 161 publications
(188 citation statements)
references
References 159 publications
(173 reference statements)
3
178
0
7
Order By: Relevance
“…A more recent retrospective, multi‐institutional study of 203 patients who underwent PM for CRC found that adjuvant chemotherapy had a positive impact on overall survival . Given the lack of level I evidence, a common approach for many multidisciplinary teams is to extrapolate on data demonstrating the disease‐free and overall survival benefit for resected stage III CRC and use similar regimens in conjunction with PM, either in a neoadjuvant or adjuvant setting . Giving induction therapy to patients with a larger burden of disease may avoid unnecessary surgery should they progress.…”
Section: Perioperative Systemic Therapymentioning
confidence: 99%
See 4 more Smart Citations
“…A more recent retrospective, multi‐institutional study of 203 patients who underwent PM for CRC found that adjuvant chemotherapy had a positive impact on overall survival . Given the lack of level I evidence, a common approach for many multidisciplinary teams is to extrapolate on data demonstrating the disease‐free and overall survival benefit for resected stage III CRC and use similar regimens in conjunction with PM, either in a neoadjuvant or adjuvant setting . Giving induction therapy to patients with a larger burden of disease may avoid unnecessary surgery should they progress.…”
Section: Perioperative Systemic Therapymentioning
confidence: 99%
“…However, the available data only support a weak recommendation for manual palpation . More recently, as CT detection has improved, expert consensus has shifted more in favor of minimally invasive approaches in oncologically and medically appropriate patients due to shortened hospital stays and decreased impact on quality of life . Data from nonrandomized studies have demonstrated that approximately 25% of patients had additional nodules identified on manual palpation, even when 3‐mm slices with high‐resolution CT scans were used .…”
Section: Operative Techniquementioning
confidence: 99%
See 3 more Smart Citations